PEMBERIAN PUPUK KANDANG AYAM DAN ABU JANJANG KELAPA SAWIT PADA BIBIT KAKAO (Theobroma cacao L.) - Edi Susilo; Wardati Wardati; Isnaini Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research aims to determine the interactionof chicken manure and oil palm bunch ashand to get the best dose to the cocoa seedlings growth. This research has been carried out in the experimentalstation Faculty of Agriculture, University of Riau from June to September 2016. This research used a completely randomized design (CRD) two factors with three replications. The first factor is the chickenmanure with four levels namely 0, 10, 15 and 20 tons/ha. The second factor was the oil palm bunch ash with three levels namely 0, 2 and 3 tons/ha. Parameters observed were plant height, girth trunk, number of leaves, root volume, the weight of dry biomass andshoot and roots ratio. The results showed that the interaction of chicken manure and oil palm bunch ash significantly a effect on plant height and shoot and roots ratio, the best treatment can be obtained by providing a dose of chicken manure 20 tons/ha and oil palm bunch ash dose of 3 tons/ha. Chicken manure gives the best treatment results with dose of 20 tons/ha significantly effect on plant height, number of leaves, root volume, biomass dry weight and shoot and roots ratio. Provision of oil palm bunch ash to the cocoa seedlings affect only the root volume and the best treatment is on oil palm bunch ash dose of 2 tons/ha.Keywords: Chicken minure, Oil palm bunch ash, Cocoa seedlings